Monastic archives and the law: legal strategies at Farfa and Monte Amiata at the turn of the millennium. - Maskarinec, Maya (Early Medieval Europe, 2021)
This article investigates two controversies that reveal the deeply intertwined nature of legal strategies and archival practices at the monasteries of Farfa and Monte Amiata around the turn of the millennium. It argues that the protagonists of these cases, abbots knowledgeable in law and the history of their monasteries, pursued markedly historical legal strategies: legal strategies that looked to, manipulated, and, above all, contextualized, archival documents in order to make legal arguments. This sheds light on early medieval monastic legal culture in north‐central Italy and provides insights into the rationale for monastic forgeries of documentary materials at Monte Amiata.